Pengaruh Pengurangan Jagung Sebagai Sumber Pati terhadap Laju Alir Pellet Pada Proses Produksi Berkesinambungan - Yuli Retnani; Reani Syafrina Rachman; Heri Ahmad Sukria (Agricultural Faculty, 2010)
The effect of reduction of maize as starch source on flow rate of pellet in continuous production processABSTRACT. This experience was conducted to determine effect of reduction of maize as starch source on flow rate of pellet in continuous production process. Design of the experiment used was a completely randomized design with 3 treatments and 3 replicates. The data is analyzed by using of ANOVA and if there is a significance among treatments would tested using by contrast orthogonal. The variables observed were angle of repose, loose bulk density, compacted bulk density, and flow rate. The results showed that the reduction of maize as starch source did not give the significant effect on the variable that observed. The analyzed angle of repose showed variation 24.200 to 25.690, loose bulk density showed variation 621.6kg/m3 to 658kg/m3, compacted bulk density showed variation 668.3kg/m3 to 676.8kg/m3, and flow rate showed variation 449.69kg/minute to 491.41kg/minute. Based on the result that the reduction of maize as starch source (corn, sorghum, menir) did not give the significant effect on flow rate of pellet and the pellet treatment with menir has the fastest pellet production time so flowability pellet from pelleter to material hadling (bucket elevator) machine is faster. As higher the values of flow rate, so the time of material movement from bin to the package is shorter.